The Relationship between the Best Practices of Transformational Leadership and Quality of Good Teachers - Fang, Jane Teng Yan; Zakaria, Thuraiya; Shokory, Suzyanty Mohd (International Journal of Economics, Business and Management Studies, 2013)
It has been reported that transformational leadership impacts significantly the teachers and schools. It has also been argued that transformational leadership principles applied to teacher development is one possibility for achieving the desirable qualities among teachers. The study investigated the relationship between transformational leadership and the quality of good teachers. The study employed a quantitative paradigm. A self-developed instrument was established. A total of 776 participants responded to the survey. The findings demonstrate the best five components of quality amongst good teachers. The results also revealed the five sets of best practices within transformational leaders. The resuts yielded that there is a significant relationship between transformational leadership and quality of good teachers. In short, the findings inform that the best practices amongst transformational leadership which are perpetual desire for continuous learning, risk taking and value driven contributed significantly towards the development of desirable qualities in teachers. It is recommended that every effort be made by the education policy to promote the practice of transformational leadership.